Intra-abdominal pressure, renal resistive index, sublingual microcirculation and total body water for guidance of volume resuscitation to avoid acute kidney injury during shock therapy - Sereina Roffler; Hannah Büchler-Fehlberg; Anna Dietz; Rita Achermann; Markus Aschwanden; Daniel Staub; Caroline Kiss; Michael Dickenmann; Caroline Eva Gebhard; Alexa Hollinger; Martin Siegemund (Renal Replacement Therapy)
Abstract Background/objectives Shock and accompanying acute kidney injury (AKI) as a frequent complication is a well-known cause of morbidity and mortality worldwide. The current standard parameters to guide fluid resuscitation therapy (i.e., cardiac output, heart rate, blood pressure, central venous pressure) to avoid AKI and renal replacement therapy remain imprecise, and fluid overload with consequent organ oedema and high intestinal pressures result in further complications. The VoluKid study investigated additional non-invasive fluid volume parameters including assessment of total body water (TBW), renal vascular resistance [renal resistive index (RRI)], intra-abdominal pressure (IAP) and microcirculatory blood flow (MBF) to predict AKI during the first 72 h of intensive care therapy. Methods, design and analysis This mono-centre observational cohort study included patients with shock who presented to the intensive care unit (ICU). Routine volume resuscitation parameters (i.e., cardiac output, heart rate, blood pressure, central venous pressure) were used to guide fluid therapy. In addition, four parameters, including MBF using sublingual incident dark-field microscopy, IAP, RRI assessed by duplex-sonography, and TBW using bioimpedance analysis (BIA), were measured daily and evaluated for predicting the primary outcome of acute kidney injury (AKI) and need for renal replacement therapy within the first 72 h of admission. Baseline and post-ICU admission values of these parameters were compared between patients with and without AKI. Results A total of 45 patients were enrolled in this study. Of those 45 patients, 37 could be followed for the entire study period of 72 h and 14 patients developed AKI (31.1%). Twelve patients (26.7%) had pre-existing renal impairment, one of whom died during the observation period. Nineteen patients (42.2%) had no renal impairment. RRI and IAP did not differ between patients with AKI and without AKI and did not predict AKI. TBW measured by BIA predicted AKI (p = 0.029). After adjustment for covariates (age, body mass index,and gender) this prediction was not significant [adjusted odds rato (OR) 0.99, p = 0.258, 95% confidence interval (CI) [0.97,1.01]]. MBF could not be estimated due a high number of missing values. Conclusions Based on our limited data, none of the non-invasive parameters (TBA, IAP, RRI,) serve as predictors for AKI when assessed during the first 72 h after ICU admission, either when analysed separately or in combination. Registration ClinicalTrials.gov Identifier: NCT02666404, registered 28/01/2016; URL: https://classic.clinicaltrials.gov/ct2/show/NCT02666404 .